2010
DOI: 10.1016/j.seizure.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Is elevated pre-ictal heart rate associated with secondary generalization in partial epilepsy?

Abstract: We report elevated heart rate prior to partial seizure onset in those attacks which become secondarily generalized compared to seizures which remain localized. The finding may be relevant for the understanding of sudden death in epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 26 publications
3
44
0
2
Order By: Relevance
“…The mean HR differences of SPS, CPS and CPS-G were (47.5 ± 24.9), (51.2 ± 19.8) and (80.5 ± 21.3) BPM, respectively. The HR changes in CPS-G seizures were the highest of the three types ( P < 0.01) (Table 3), which has been reported previously [23,11]. …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The mean HR differences of SPS, CPS and CPS-G were (47.5 ± 24.9), (51.2 ± 19.8) and (80.5 ± 21.3) BPM, respectively. The HR changes in CPS-G seizures were the highest of the three types ( P < 0.01) (Table 3), which has been reported previously [23,11]. …”
Section: Discussionsupporting
confidence: 86%
“…Analysis shows that HR increases significantly in CPS-G compared to non-generalized seizures [10]. More insight into the mechanisms of generalization of partial seizures may improve treatment, and possibly also contribute to a reduced number of SUDEP, which has been reported previously [11]. HR increase seems more prominent in temporal lobe seizures (where insular spread is common), compared with extratemporal seizures [12-14].…”
Section: Introductionmentioning
confidence: 93%
“…In another study in children, ictal tachycardia was present in 70% of focal seizures (temporal or frontal onset), but not in A c c e p t e d M a n u s c r i p t generalized seizures [75]. One interesting study found that heart rate increased from the preictal to the ictal period in 74% of the patients and it was higher in seizures with secondary generalization than in complex partial seizures [76]. One of the few studies that included generalized seizures detected heart rate changes in 35% of seizures, either GTCS or secondarily generalized seizures [65].The sensitivity of the automated detection algorithms was 90-98% in seizures with heart rate changes, with a greater than 50% positive predictive value [64,77].…”
Section: Electrocardiogram (Ekg)mentioning
confidence: 92%
“…Chronic epileptiform discharges or epileptic foci in these areas may produce potentially life-threatening cardiac arrhythmias both ictally and interictally as cardiovascular regulation is, in fact, a function of neuronal activity in the cerebral cortex, the amygdale, and the medullary reticular formation [18, 29, 4346]. It has been suggested in the context of increased preictal HR that in patients with primarily more instability and activation in cortical networks surrounding the seizure onset zone will simultaneously increase sympathetic tone and risk for generalization of the seizure, since noradrenergic function may be needed for the anticonvulsive effect of the vagus nerve stimulation, at least in animals [47]. However, on the other hand, it has also been shown that secondarily generalized seizures lead to higher ictal HR and sustained postictal tachycardia with enhanced shortening of QT-interval possible showing that cardiac alterations are in fact a link between generalized seizures and SUDEP [48].…”
Section: Discussionmentioning
confidence: 99%